Tree-ring [delte]2H values from lignin methoxyl groups indicate sensitivity to European-scale temperature changes - Anhäuser, Tobias; Sehls, Birgit; Thomas, Werner; Hartl, Claudia; Greule, Markus; Scholz, Denis; Esper, Jan; Keppler, Frank (Palaeogeography, palaeoclimatology, palaeoecology, 2020)
Stable hydrogen isotope ratios of lignin methoxyl groups (δ2HLM) of wood have been shown to reflect climate-sensitive δ2H values of precipitation (δ2Hprecip). However, a detailed calibration study between high-resolution δ2HLM and δ2Hprecip data has not been performed yet. Here, we present annually resolved δ2HLM values from nine tree-ring series (derived from four Fagus sylvatica L. trees) collected near a station of the Global Isotope Network of Isotopes in Precipitation (GNIP) and the meteorological observatory at Hohenpeißenberg (Germany; ~48°N, 11°E). The nine δ2HLM tree-ring series show highly significant inter-series correlations (Rbar = 0.52) over the common period of overlap 1916-2015 and no sign of a major juvenile trend affecting the first decades of growth. When compared with local instrumental data, the combined δ2HLM chronology is most indicative for annually averaged δ2Hprecip values. In line with this finding, the δ2HLM chronology shows similar climatic imprints as commonly observed for European stable water isotopes. We find the highest correlation (r = 0.72, p < 0.001) with temperature changes averaged over large-scale areas (range: 15°W-20°E, 25-75°N) including marine and continental Western Europe. This large-scale temperature signal is not entirely stable over time, but weakens from 1948 to 1982 where 31-year running correlations drop systematically. The temporal signal strength coincides with a decline in Rbar values but also with known anomalous atmospheric circulation events (e.g., winter of 1956). We conclude two main findings. First, the temporal robustness of the transfer model is mainly controlled by the internal coherency among the tree-ring δ2HLM series. An improved understanding of such temporal discrepancies among the proxy data may therefore optimize reconstruction models. Second, this study highlights the need to critically assess the impact of changing atmospheric circulation patterns on the relationship between climate parameters and stable water isotopes.
Im Titel ist die Zahl "2" hochgestellt
Im Titel ist delta als griechischer Buchstabe dargestellt
Gesehen am 14.05.2020